Epigenetic and transcriptomic alterations in the ClC-3-deficient mice consuming a normal diet - Jing, Zhenghui; Zhang, Haifeng; Wen, Yunjie; Cui, Shiyu; Ren, Yuhua; Liu, Rong; Duan, Sirui; Zhao, Wenbao; Fan, Lihong (Frontiers in Cell and Developmental Biology, 2023)
Metabolic disorders are an important health concern to threaten life and burden society severely. ClC-3 is a member of the chloride voltage-gated channel family, and the Clcn3 deletion improved the phenotypes of dysglycemic metabolism and the impairment of insulin sensitivity. However, the effects of a healthy diet on transcriptome and epigenetics in ClC-3-/- mice were not detailedly explained. In the present study, we found that the younger than 8 weeks old ClC-3-/- mice had smaller bodies compared to ClC-3+/+ mice with ad libitum self‑feeding normal diet, and the older than 10 weeks old ClC-3-/- mice had similar body weight. Except for the spleen, lung, and kidney, the average weight of the heart, liver, and brain in ClC-3-/-mice was lower than those in ClC-3+/+ mice. TG, TC, HDL, and LDL in fasting ClC-3-/- mice were not significantly different from those in ClC-3+/+ mice. Fasting blood glucose in ClC-3-/- mice was lower than that in ClC-3+/+ mice; the glucose tolerance test indicated the response to blood glucose increasing for ClC-3-/- mice were torpid, but the efficiency of lowering blood glucose was much higher once started. Transcriptomic sequencing and Reduced Representation Bisulfite Sequencing for the liver of unweaned mice indicated that Clcn3 deletion significantly changed transcriptional expression and DNA methylation levels of glucose metabolism-related genes. 92 genes were intersected between DEGs and DMRs-targeted genes, of which Nos3, Pik3r1, Socs1, and Acly were gathered in type II diabetes mellitus, insulin resistance, and metabolic pathways. Moreover, Pik3r1 and Acly expressions were obviously correlated with DNA methylation levels, not Nos3 and Socs1. However, the transcriptional levels of these four genes were not different between ClC-3-/- and ClC-3+/+ mice at the age of 12 weeks old. In conclusion, ClC-3 had an influence on the methylated modification to regulate glucose metabolism, of which the gene expressions could be driven to change again by a personalized diet style intervention.